Pengaruh Economic Value Added Momentum (EVAM), Debt Equity Ratio (DER), Net Profit Margin (NPM), Return On Asset (ROA), Return On Equity (ROE) Terhadap Kinerja Pasar (Studi Empiris pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia) 2010-2014 - Widodo, Arif Wahyu, Dr. Fatchan Achyani, S.E, M.Si (2016)
This study was conducted for the purpose of evaluating the correlation between EVA Momentum, DER, NPM, ROA, ROE on the performance of the market. Where the performance of the market (which is projected to the stock return and MVA). The population used in this study are all banks listed on the Indonesia Stock Exchange amounted to 36. The sampling method with a purposive sampling according to criteria that have been determined. The number of samples collected as many as 14. With the amount of data as much as 70, because of the outliers by 2 then the data becomes 68. The collected data were analyzed using data analysis conducted prior classic assumption test before hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test, f-test, and the coefficient of determination. The results show that DER, NPM, ROA, and ROE don't have significant effect on stock returns. While EVA Momentum variable has significant effect on stock returns. The results show that the EVA Momentum, DER, ROA, ROE don't have significant effect on MVA. Meanwhile, NPM variable has significant influence on MVA. This is accordance with the results of multiple linear regression test and partial test. The test results show that EVA Momentum, DER, NPM, ROA, ROE have effect on stock returns and MVA simultaneously.